2009
DOI: 10.1098/rspb.2009.1774
|View full text |Cite|
|
Sign up to set email alerts
|

A photoactivatable green-fluorescent protein from the phylum Ctenophora

Abstract: Genes for the family of green-fluorescent proteins (GFPs) have been found in more than 100 species of animals, with some species containing six or more copies producing a variety of colours. Thus far, however, these species have all been within three phyla: Cnidaria, Arthropoda and Chordata. We have discovered GFP-type fluorescent proteins in the phylum Ctenophora, the comb jellies. The ctenophore proteins share the xYG chromophore motif of all other characterized GFP-type proteins. These proteins exhibit the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Ctenophore FP clustered with hydrozoan FP, therefore the cnidarian clade was not monophyletic. Others have shown that incongruence with taxonomy is not unusual in fluorescent proteins [43]. For better visualization, a smaller maximum likelihood sub-tree was generated from 46 scleractinian FP sequences (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Ctenophore FP clustered with hydrozoan FP, therefore the cnidarian clade was not monophyletic. Others have shown that incongruence with taxonomy is not unusual in fluorescent proteins [43]. For better visualization, a smaller maximum likelihood sub-tree was generated from 46 scleractinian FP sequences (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Photophores (bioluminescent organs) in fact often convert their naturally blue bioluminescent light to green using what is aptly named 'green fluorescent protein' (GFP). This is common in jellyfish and other cnidarians and may be used to increase visibility range in greener coastal waters where this conversion is common [27]. Orange and red light is also made by fluorophores converting blue bioluminescence and potentially ambient light in deeper-sea bioluminescent species [28,29].…”
Section: (C) Spectral Sensitivity Ranges Of Potential Viewersmentioning
confidence: 99%
“…Haddock and co-workers [27,29,40] have made the case that some hydromedusan gelatinous zooplankton species construct fluorescent lures to bring in prey. This includes the tentacle tip (tentilla) in Erenna, a deep-sea, fish-eating siphonophore with fluorescent tissue emitting yellow to red (583-680 nm) surrounding a bioluminescent photophore.…”
Section: (E) Birdsmentioning
confidence: 99%
“…To date, GFP-like proteins have been found in several distant groups of marine animals: in two classes [the hydroid jellyfishes Hydrozoa (Prasher et al, 1992) and the coral polyps Anthozoa (Matz et al, 1999)] of the phylum Cnidaria; in one species from the comb jelly phlyum Ctenophora (Haddock et al, 2010); in several species of copepods (phylum Arthropoda; Shagin et al, 2004) and in lancelets (phylum Chordata; Deheyn et al, 2007). The greatest spectral diversity has been demonstrated for Anthozoa GFP-like proteins.…”
Section: Introductionmentioning
confidence: 99%